Hot Rods and Exploding Ova - Walddon, David; Malmstrom, Dawn (Petits Propos Culinaires, 2015)
The Martino corpus of cookery manuscripts has been explored in depth; early on in Platina and the Rebirth of Man, in the comprehensive edition and translation, as well as the older standard translation of De Honesta Voluptate (On Honest Indulgence), in papers given at the Oxford Symposium on Food and Cookery, in the two translations of Martino’s Libre de Arte Coquinaria (The Book on the Art of Cooking), and in Terence Scully’s in-depth commentary on and translation of MS Bühler. However, in all of these explorations the recipe ‘Oua nel speto’ (Eggs on a spit) has not been discussed in detail and has certainly not been compared across the corpus. That is the focus of this paper which is accompanied by specially commissioned (contemporary) line drawings illustrating the techniques involved.